Hypersalivation: update of the German S2k guideline (AWMF) in short form - Steffen, Armin; Jost, Wolfgang; Bäumer, Tobias; Beutner, Dirk; Degenkolb-Weyers, Sabine; Groß, Martin; Grosheva, Maria; Hakim, Samer; Kahl, Kai G.; Laskawi, Rainer; Lencer, Rebekka; Löhler, Jan; et al. (Journal of Neural Transmission, 2019)
Hypersalivation describes a relatively excessive salivary flow, which wets the patient himself and his surroundings. It may result because of insufficient oro-motor function, dysphagia, decreased central control and coordination. This update presents recent changes and innovation in the treatment of hypersalivation. Multidisciplinary diagnostic and treatment evaluation is recommended already at early stage and focus on dysphagia, saliva aspiration, and oro-motor deficiencies. Clinical screening tools and diagnostics such as fiberoptic endoscopic evaluation of swallowing generate important data on therapy selection and control. Many cases profit from swallowing therapy programmes to activate compensation mechanisms as long compliances are given. In children with hypotonic oral muscles, oral stimulation plates can induce a relevant symptom release because of the improved lip closure. The pharmacologic treatment improved for pediatric cases as glycopyrrolate fluid solution (Sialanar®) is now indicated for hypersalivation within the EU. The injection of botulinum toxin into the salivary glands has shown safe and effective results with long-lasting saliva reduction. Here, a phase III trial is completed for incobotulinum toxin A and, in the US, is indicated for the treatment of adult patients with chronic hypersalivation. Surgical treatment should be reserved for isolated cases. External radiation is judged as a safe and effective therapy when using modern 3D techniques to minimize tissue damage. Therapy effects and symptom severity have to be followed, especially in cases with underlying neurodegenerative disease.
CRIS-Team Scopus Importer:2019-07-26
Keywords: Botulinum toxin; Drooling; Dysphagia; Glycopyrrolate; Hypersalivation; Oro-motor and oro-sensory therapy; Sialorrhea